2022
DOI: 10.1002/cam4.4716
|View full text |Cite
|
Sign up to set email alerts
|

Identification of FDFT1 as a potential biomarker associated with ferroptosis in ccRCC

Abstract: Renal cell carcinoma (RCC) is a genitourinary system tumor that seriously threatens people's lives and health. The complex pathophysiological process of RCC, which makes up approximately 16% of patients, is metastatic at the time of diagnosis and has a low 5-year relative survival rate, resulting in more than 65,000 new cases being diagnosed and almost 15,000 deaths every year in the United States. 1 There are three major histological subtypes of RCC, including clear cell RCC (ccRCC), papillary RCC (pRCC), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Current studies have shown that these genes are associated with the prognosis of multiple cancers and can be used as independent risk factors for tumors. [30][31][32][33][34][35][36] Consensus clustering with this 10 gene expression signature identi ed three genomic subtypes with similar results to the ferroptosis phenotype cluster. Similarly, using survival analysis, GSVA enrichment analysis, and immune cell in ltrate signature analysis, we demonstrated that overall TME in ltration mediated by multiple FRG types was strongly associated with overall survival in osteosarcoma patients again.…”
Section: Discussionmentioning
confidence: 96%
“…Current studies have shown that these genes are associated with the prognosis of multiple cancers and can be used as independent risk factors for tumors. [30][31][32][33][34][35][36] Consensus clustering with this 10 gene expression signature identi ed three genomic subtypes with similar results to the ferroptosis phenotype cluster. Similarly, using survival analysis, GSVA enrichment analysis, and immune cell in ltrate signature analysis, we demonstrated that overall TME in ltration mediated by multiple FRG types was strongly associated with overall survival in osteosarcoma patients again.…”
Section: Discussionmentioning
confidence: 96%
“…FDFT1 encodes a membranelinked enzyme, which constituted the rst speci c enzyme in cholesterol biosynthesis [23]. Recent study showed that increased expression of FDFT1 could potentially enhance ferroptosis through the AKT signaling pathway, but the speci c molecular mechanism remains unclear [24]. Weng et al demonstrated that fasting suppressed aerobic glycolysis as well as CRC cell proliferation through the FDFT1/AKT-mTOR-HIF1α axis and that FDFT1 de ciency was linked to a dismal prognosis in CRC [23].…”
Section: Discussionmentioning
confidence: 99%
“…It can be an effective predictive biomarker in ccRCC, and the nomogram based on KIF23 may help with improved treatment recommendations for ccRCC patients [106]. Other studies reported that FDFT1 and acyl-CoA thioesterases 8 and 11 can be used as new biomarkers for ccRCC [107, 108]. Zhu et al [109] indicated that ZNF419 had the potential to serve as a prognostic and immunological pancancer biomarker, particularly for KIRC, LIHC, LUSC, PRAD, and BLCA.…”
Section: Ferroptosis and Kidney Diseasesmentioning
confidence: 99%